Development of a recombinant non-replicating Newcastle disease virus - Cheow, Pheik-Sheen; Tan, Tiong Kit; Song, Adelene Ai-Lian; Yusoff, Khatijah; Chia, Suet Lin (Taylor and Francis, 2024)
Newcastle disease virus (NDV) is an avian orthoavulavirus I that causes high morbidity and mortality in birds, depending on the pathotype of the virus. Several clinical studies have shown that NDV is a promising oncolytic virus for cancer therapies, yet its application to clinics is restricted due to the pathogenicity of this virus in poultry. Hence, it is important to produce a recombinant NDV (rNDV) with reduced virulence to make it a fit candidate as an oncolytic virus. In this study, we aimed to produce a rNDV with a truncated ant-igenome via reverse genetics to render it non-replicating (nr). The genes responsible for replication were removed from the NDV genome. The rescued nr-NDV was verified, propagated, and purified from tissue culture medium. The virus failed to propagate in embryonated eggs, confirming its non-replicating property. The virus retained its oncolytic activities similar to that of the replicating rAF-GFP as observed in a cell viability assay when a breast cancer cell line, MCF-7, was treated with the virus. In conclusion, this study has successfully generated a system to produce a non-replicating NDV which can be used as a viral vector for heterologous protein delivery, as a safer alternative compared to the virulent strains as an oncolytic virus. RESEARCH HIGHLIGHTS: Development of nr-NDV. Reverse transfection was applied for the recovery of nr-NDV. Propagation of nr-NDV was done by sub-passaging transfected BSR T7/5 cells. Safety profile was done to prove that the nr-NDV is non-replicating.